Foundation chemistry Class 8 - Gautam, Ashutosh 1965-; Kalwadia, Bela (NVision, 2025)
Pearson NVision Series is a range of books to help learners go beyond the school curriculum and attain competitive edge. Based on the latest NCERT curriculum, NVision chapters begin with theoretical concepts, closely accompanied with in-text exercises, checkpoints, important notes, solved examples, diagrams, tables, and activities. The concepts and exercises in the book are designed to prepare students for exams such as JEE, NEET, and Olympiads like NSO, IOM, IMO, NSTSE, and IOS. The exercises are divided into three levels of difficulty, helping learners first understand the concepts, then apply them, and finally practice previous years' questions to become exam ready.